An upcycled wood sponge adsorbent for drinking water purification by solar steam generation. Issue 7 (15th June 2022) - Li, Meng; Xu, Mengwen; Shi, Quanyu; Wang, Haotian; Guo, Hongmin; Wang, Lidong; James, Tony D.
Abstract : A 3D-MoS2 based wood sponge absorbent was upcycled to construct a solar steam generator for drinking water purification. Abstract : The shortage of freshwater resources caused by heavy metal pollution is an acute global issue. Herein, a novel nanoplatform was fabricated by hydrothermal deposition of 3D-MoS2 nanospheres onto biocompatible wood sponge (WS) for Hg(ii ) removal. Moreover, a secondary water purification strategy was investigated to produce drinkable water using the exhausted wood sponge. The exhausted MoS2 -wood sponge (MWS) was used to construct a solar steam generator by wrapping with a hydrophilic polyvinyl alcohol (PVA) layer to prevent heavy metal ion leakage and to enhance the hydrophilicity. The energy conversion efficiency of the evaporator was calculated to be 95.48% under one sun illumination. Remarkably, the treatment of model desulphurization wastewater from power plants with this functional wood sponge could efficiently reduce the mercury concentration below the limit proposed by the World Health Organization for drinking water. These results provide a basis for the application of upcycled hazardous adsorbents for the purification of drinkable water.